Primary mucinous cystadenoma of the spermatic cord within the inguinal canal - Kim Jee-Yeon; Lee Young-Taek; Kang Hyun-Jeong; Lee Chang-Hun (BMC, 2012)
Abstract We report a hitherto not documented case of primary mucinous cystadenoma arising in the spermatic cord within the right inguinal canal of a78-year-old man. The tumor was painless, hard and mobile. A computed tomography scan on the pelvis revealed an oval shaped, low attenuation mass, measuring 5.0x2.5x2.1 cm, that was present adjacent to the vas deferens. Grossly, the excised mass was multicystic mucinous tumor, filled with thick mucoid materials. Microscopically, the cystic wall was irregularly thickened. The cystic epithelium commonly showed short papillae lined by a single layer of columnar to cuboidal mucinous epithelial cells without significant stratification or cytologic atypia. Goblet cells were also frequently present. Immunohistochemically, the neoplastic cells showed positive reaction to carcinoembryonic antigen, cytokeratin 20, CDX2, epithelial membrane antigen, and CD15. However, they were negative for PAX8 and Wilms' tumor 1 protein. Pathological diagnosis was a papillary mucinous cystadenoma of the spermatic cord. Although mucinous cystadenoma in this area is extremely rare, it is important that these lesions be recognized clinically and pathologically in order to avoid unnecessary radical surgery. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1720965948762004